A Case Report of Pulmonary Exacerbation after Initiation of Lumacaftor/Ivacaftor Therapy in a CF Female with Complicated Lung Disease - Elpis Hatziagorou; Eleana Kouroukli; Vasiliki Georgopoulou; John Tsanakas (Case Reports in Pulmonology)
Novel targeted treatments for Cystic Fibrosis give rise to new hope for an ever-growing number of CF patients with various mutations. However, very little evidence and guidelines exist to steer clinical decisions regarding patients whose illness takes an unexpected course. In such cases, the benefits and risks of discontinuing these treatments must be carefully and individually weighed, since their long-term effects remain mainly uncharted territory. In this report we document the case of a homozygous F508del CF patient with severe lung disease who presented with a pulmonary exacerbation shortly after the beginning of treatment with lumacaftor/ivacaftor and the complicated initial phase of therapy, which was followed by significant improvements.